The Genus Fragaria in Croatia - Dujmović Purgar, Dubravka; Duralija, Boris; Vokurka, Aleš; Todorić, Marija; Židovec, Vesna (Erwerbsobstbau, 2017)
Only three native species of genus Fragaria ( F. moschata, F. vesca and F. viridis ) are recorded in three regions of Croatia. These species as well as many of their hybrids, are, or once were, cultivated for their edible fruits. The majority of cultivated strawberries in Europe belong to garden strawberries F. x ananassa (hybrids of F. chiloensis and F. virginiana ). The most expanded wild strawberry species in Croatia is a woodland strawberry ( F. vesca ) whose berries are gathered seasonally as wild edible fruits. They often contain higher amount of nutrients and bioactive compounds in comparison to cultivated varieties. The research on the genus Fragaria species distribution in Croatia has not been carried out, and so is the case with many others wild growing fruit species in Croatia. By summing up a number of individual citations and observations, it is possible to get a perspective regarding the current state of their distribution.